نظام إنشاء شركة إعادة التكافل في ماليزيا: دراسة تحليلية - Laeba, Muhammad; Duramea, Ismail (Besiz Publications, 2016)
تعد ماليزيا من الدول المتقدمة في تأسيس أنظمة خاصة لصناعة التكافل وإعادة التكافل بشكل عام، وقد واجهت منذ تأسيسها للأنظمة عدة تحديات وعقبات بذلت قصارى جهدها في إيجاد الحلول لها رغم الصعوبات التي كانت تقف أمامها أهمها التحدي الاجتماعي والديني والثقافي والسياسي؛ وقد استطاعت _بتوفيق من الله أولا وأخرا_ بإصرار العلماء والباحثين والمهتمين وبالدعم المتواصل من قبل الحكومة في تهيأت الجو المناسب وتقديم كل التسهيلات والخدمات التي ساعدت في نجاح وتطور هذه الصناعة؛ وفي هذا البحث المتواضع سيحاول الباحث تسليط الضوء على أنظمة إنشاء شركة إعادة التكافل في ماليزيا التي تعد من أهم القضايا الحساسة التي واجهت القائمين على هذه الصناعة، ودراسة أهم الجوانب الايجابية والسلبية فيها. ************************************************************ Generally Malaysia is one of the Developed Countries in the Establishment of special regulations for Takaful and Retakaful Industries, it faced by many challenges and obstacles since the establishement of such kind of regulations; where it spent tireless effort in addressing them despite many difficulty in doing so. Among the critical challenges are Social, religious, cultural and political challenges. By the grace of Allah Malaysia was able to tackle such problems tharough the tireless effort given by scholars and researchers aswell as the constant government support in providing any services for the development and success of this industry. The researcher is going to humbly shade light on the regulations of the establishment of Takaful industry in Malaysia which is one of the sensitive issues to face the organizers of this industry. Futhermore, the significant positive and negative aspect of this matter will also be discussed.